2013
DOI: 10.1371/journal.pone.0071022
|View full text |Cite
|
Sign up to set email alerts
|

NCI-H295R, a Human Adrenal Cortex-Derived Cell Line, Expresses Purinergic Receptors Linked to Ca2+-Mobilization/Influx and Cortisol Secretion

Abstract: Purinergic receptor expression and involvement in steroidogenesis were examined in NCI-H295R (H295R), a human adrenal cortex cell line which expresses all the key enzymes necessary for steroidogenesis. mRNA/protein for multiple P1 (A2A and A2B), P2X (P2X5 and P2X7), and P2Y (P2Y1, P2Y2, P2Y6, P2Y12, P2Y13, and P2Y14) purinergic receptors were detected in H295R. 2MeS-ATP (10–1000 µM), a P2Y1 agonist, induced glucocorticoid (GC) secretion in a dose-dependent manner, while other extracellular purine/pyrimidine ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
(80 reference statements)
1
19
0
Order By: Relevance
“…In fact, considering all genotypes, we were able to demonstrate a positive correlation between tumor size and tumor AMP and ADP content, respectively. Furthermore, purines, including ATP, ADP, and AMP, have been shown to stimulate steroidogenesis in bovine adrenal cells (30) potentially by inhibition of noninactivating K + current, thereby modulating the resting membrane potential (31) and increasing intracellular Ca 2+ levels (32). Therefore, it is prudent to speculate that abundant purines in KCNJ5-mutated APAs could contribute to or modify steroidogenesis as auto-or paracrine signals.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, considering all genotypes, we were able to demonstrate a positive correlation between tumor size and tumor AMP and ADP content, respectively. Furthermore, purines, including ATP, ADP, and AMP, have been shown to stimulate steroidogenesis in bovine adrenal cells (30) potentially by inhibition of noninactivating K + current, thereby modulating the resting membrane potential (31) and increasing intracellular Ca 2+ levels (32). Therefore, it is prudent to speculate that abundant purines in KCNJ5-mutated APAs could contribute to or modify steroidogenesis as auto-or paracrine signals.…”
Section: Discussionmentioning
confidence: 99%
“…A functional P2RY1 is needed for intracellular Ca²⁺ mobilization, a process that is linked to store‐operated calcium entry activation, leading to Ca²⁺ influx, which may be necessary for glucocorticoid secretion (Nishi et al . ). RAP2B is a member of GTP‐binding proteins that are widely upregulated in many types of tumors and promotes migration and invasion of human suprarenal epithelioma.…”
Section: Significant (False Discovery Ratementioning
confidence: 97%
“…Moreover, it was reported that NCl-H295R (a human adrenal cortex-derived cell line) expressed multiple purinergic receptors and P2Y1 was related to glucocorticoid secretion [16]. The results of the present study demonstrated that the binding site of GTP seems to be completely different from that of ATP (Fig.…”
Section: Effects Of Gtp On Cyclic Amp Formation and Cytosolic Calciummentioning
confidence: 45%